Multilingual database management system: a performance evaluation - Mohd Saad, Nurul Husna; Ibrahim, Hamidah (Science Publications, 2011)
Problem statement: The use of English as well as Arabic language is increasingly evident in the aspects of international business and finance. Therefore, this study explored the management of multilingual data in multilingual system in order to be able to cater two or more different speakers of Internet users. Approach: The proposed method is divided into two ends: The front-end that consisted of the Client and the Translator components and the back-end where the Management Module and the Database are located. In this method, a single encoded table is needed to store information and corresponding dictionaries are needed to store the multilingual data. The proposed method is based on the framework proposed in previous work with some modification to suit with the characteristics of the chosen languages on the case study. Results: Experimental evaluation had been done in storage requirement and mathematical analysis had been used to show the time of each of database operations for both of the traditional and the proposed method. Conclusion/Recommendations: The proposed method had been found to be consistently performed in the developed multilingual system.